Integrasi Green Chemistry pada Proses Pembelajaran - Winda Putri Permata Sari; Sri Atun (Postgraduate, University of Mataram, 2023)
This research aims to synthesize the related research with green chemistry as the topic which focuses on chemistry learning research in the recent ten years from various Scopus journals and proceedings focusing on the recent ten years. After doing the searching on the national and international reputable databases by using the relevance key pattern (Pattern 1: â€œgreen chemistryâ€ â€œgreen chemistry learningâ€; Pattern 2: â€œgreen chemistryâ€ â€œcurriculaâ€; Pattern 3: â€œgreen chemistryâ€ â€œchemistry education), from 20 relevant articles to be systematically reviewed. The systematic goal is to result in the general review and knowledge for teachers about the integration of green chemistry in the learning process. At the middle school level, the integration of green chemistry through project-based practicum activities, textbooks, modules, and games. The result shows that the chemistry topic which can be integrated with green chemistry is by making soap, fossil fuels, recycling processes, environmental problems arising from the use of fuel, chemical reactions, and plastic waste. While 12 green principles in some articles are discussed thoroughly while others donâ€™t. There are only 5 or 6 green chemistry principles integrated either in modules, games, and practicum activities. By doing the research, it is expected to give knowledge to the teachers related to green chemistry integration in the process of learning to support the Merdeka curriculum in chemistry learning.